2021
DOI: 10.38007/kme.2021.020106
|View full text |Cite
|
Sign up to set email alerts
|

Visual Intelligent Recognition System based on Visual Thinking

Abstract: Image semantic segmentation plays an important role and has application value in robot arm object capture, automatic driving, medical image analysis, geographic information system, etc. Aiming at the semantic segmentation method of deep learning(DL), this paper makes some attempts in the direction of weak supervised semantic segmentation, proposes AI and DL technology, and applies them to the Image segmentation technology(IST) in the construction machinery(CM) grasping task for analysis and exploration. The im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…From the data in Table 2, it can be seen that in the process of segmenting remote sensing image edges in this paper, the CPU utilization rate was all below 4%, and the average segmentation time for each region was only about 12 ms, with an edge segmentation error of no more than 1%. This also indicated that the ecological landscape segmentation system in this paper had high efficiency, strong stability, and low resource consumption in remote sensing images, demonstrating superior image segmentation performance (Kavita, 2021;Yang et al, 2022).…”
Section: System Analysis Layermentioning
confidence: 64%
“…From the data in Table 2, it can be seen that in the process of segmenting remote sensing image edges in this paper, the CPU utilization rate was all below 4%, and the average segmentation time for each region was only about 12 ms, with an edge segmentation error of no more than 1%. This also indicated that the ecological landscape segmentation system in this paper had high efficiency, strong stability, and low resource consumption in remote sensing images, demonstrating superior image segmentation performance (Kavita, 2021;Yang et al, 2022).…”
Section: System Analysis Layermentioning
confidence: 64%
“…As digital images have the characteristic of matrix storage, they particularly rely on the image computing capabilities of hardware devices in image processing technology [8]. The utilization efficiency of traditional image generation methods is also related to the realism of image application scenarios, graphic generation, and the complexity of establishing virtual scenes that meet the requirements [9]. Although this type of drawing software has been highly encapsulated, the various functions inside are actually based on traditional graphic processing algorithms.…”
Section: Image Generationmentioning
confidence: 99%